Histopathological changes in liver and gills of Odontesthes bonariensis inhabiting a lake with high concentrations of arsenic and fluoride (Chasicó Lake, Buenos Aires Province) - Puntoriero, María Laura (2018)
Water bodies in the Chaco-Pampean plain contain arsenic (As) and fluoride (F-) occurring naturally. Chasicó Lake, located in the southwest of Buenos Aires Province, has high concentrations of both elements (As, 0.05-0.41 mg/L; F-, 6.74-8.54 mg/L). Fish can be considered as indicators of environmental pollution. The aim of this study was to analyze whether the presence of high concentrations of As and F- found in the liver and gills of Odonthestes bonariensis could be associated to histological changes found in these tissues. Fish were sampled from different locations of the lake. Tissue samples (liver and gills) were subdivided and subjected to an acid digestion to determine As and to an alkaline digestion to determine F-. Morphological changes were assessed using routine histological techniques. As concentrations in the liver were higher than in the gills, while the gills showed higher F- concentrations. The histological examination of the liver and gills showed alterations that could correspond to the effects of the high As and F- concentrations found in these tissues. The toxicity of these elements is due to oxidative stress. Silverside is one commercially relevant fish in Buenos Aires and a key species in the food chain in the region. Therefore, further histopathological studies are relevant to guarantee this fish’s health and safety for human consumption.